Pemikiran Cak Nun tentang Harmoni Budaya dan Teknologi dalam Ruang Keagamaan - Laelani, Rizki; Mukarom, Zaenal (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This article analyzes Emha Ainun Nadjib's (Cak Nun) thoughts on the relationship between religion, culture, and technology from the perspective of contemporary Islamic communication. Based on the YouTube video "Cak Nun: Religion and Culture" from @UniversitasKehidupan, Cak Nun emphasizes that Islamic da'wah requires cultural and technological mediums to effectively convey messages in modern society. This study positions Cak Nun as a da'wah communicator employing humanistic and contextual approaches through culturally-based strategies and digital media integration. Using Cultural Transactional Communication Theory and Cultural Adaptation Theory, the research examines how Cak Nun's da'wah represents a dialogical, participatory, and adaptive communication model. Concrete examples include technological management of Zamzam water and Muslim fashion production, demonstrating how technology supports Islamic values actualization in daily life. The analysis highlights Cak Nun's effective multimedia da'wah communication via digital platforms for religious literacy and collective Islamic consciousness cultivation. This article contributes to Islamic communication theory and practice development, responsive to contemporary socio-religious dynamics. The study underscores media literacy urgency in da'wah and innovation importance in delivering Islamic messages digitally. Cak Nun's approach serves as a cultural-modern da'wah model integrating Islamic teachings with contextual, inclusive, and transformative communication strategies.